Analisis Nilai Pendidikan Karakter dalam Pembelajaran Bahasa Indonesia Siswa Kelas XI SMAN 4 Sinjai - Irnawati, Irnawati; Usman, Usman; Dewi, Anita Candra (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to describe the planning, implementation, and assessment of character education in Indonesian learning in grade XI students of SMAN 4 Sinjai. This study uses a descriptive qualitative approach. Data collection was carried out through interviews, observations, and documentation. The research instruments include a checklist of observation guidelines, interview guidelines, and document analysis in the form of learning modules. The results of the study show that Indonesian learning in grade XI of SMAN 4 Sinjai has integrated character education, especially discipline, responsibility, and cooperation in planning, implementation, and learning assessment. The implementation of character values is carried out through discussions, group work, and teacher examples, while assessment is carried out through observation of students' attitudes during learning. The obstacles faced include the influence of the family environment, time constraints, and inconsistency in the application of character values. This study concludes that the implementation of character education has been quite effective, but it needs to be strengthened through value-based literacy activities and contextual learning. The contribution of this research lies in the presentation of good practices in the implementation of contextual character education at SMAN 4 Sinjai as a reference for Indonesian language learning.